Cardiorespiratory adaptation to sport in young school boys - Senatorova, G. S.; Onikiienko, O. L. (Journal of Education, Health and Sport, 2018)
There is insufficient number of researches dedicated to cardiorespiratory adaptation in various physical activities in general, and especially in children and adolescents for certain types of sport. The objective: to determine the cardiorespiratory adaptation features in boys of primary school age engaged in football. Material and method. The study involved data from 92 male children aged 10-11 years, of which 68 children attended sports football schools. The study design included a general clinical examination, a spirometry, condition of cardiovascular system assessed with echocardiography, exercise stress test with cycle ergometer (VEM), 24-hours electrocardiogram (Holter - ECG) monitoring, and ambulatory blood pressure monitoring (ABPM). Results. Boys 10-11 years of age who play sports have increased values of minute respiratory volume and heart morphology indices, which reflect the myocardial hypertrophy development, although they correspond to normal Z-score values. The frequency of subjective complaints in boys who do not practice football is significantly more frequent when performing the exercise test. According to VEM, Holter-ECG and ABPM results in 57 (83.8%) of 68 football players (p=0.00393) changes were registered. Conclusions. We obtained statistically significant quantitative differences in the functional state of the cardiovascular system in children-athletes. Satisfactory cardiorespiratory adaptation of boys-athletes is documented during various stages of physical activity with the help of VEM and Holter-ECG and ABPM. The changes found in young athletes may result to further supervision of a pediatric cardiologist, but decision should made individually.